Complex magnetic behavior and high spin polarization in Fe3-xMnxSi alloys - Lezaic, Marjana; Mavropoulos, Phivos; Blügel, Stefan; Ebert, Hubert (PHYSICAL REVIEW B, 2011)
Fe3Si is a ferromagnetic material with possible applications in magnetic tunnel junctions. When doped with Mn, the material shows a complex magnetic behavior, as suggested by older experiments. We employed the Korringa-Kohn-Rostoker Green-function method within density-functional theory in order to study the alloy Fe3-xMnxSi, with 0 <= x <= 1. Chemical disorder is described within the coherent potential approximation. In agreement with experiment, we find that the Mn atoms align ferromagnetically to the Fe atoms, and that the magnetization and Curie temperature drop with increasing Mn concentration x. The calculated spin polarization P at the Fermi level varies strongly with x, from P = -0.3 at x = 0 (ordered Fe3Si) through P = 0 at x = 0.28, to P = +1 for x > 0.75; i.e., at high Mn concentrations the system is half metallic. We discuss the origin of the trends of magnetic moments, exchange interactions, Curie temperature, and the spin polarization.